STRATEGI PEMASARAN DIGITAL UNTUK MENINGKATKAN EKONOMI UMKM DI DESA PADANG SARI - Simanjuntak, Helmina; Sinaga, Saria; Sirait, Syamsinah (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
This study examines the implementation of digital marketing strategies as a solution to improve the economy of Micro, Small and Medium Enterprises (MSMEs) in Padang Sari Village. In the era of digitalization, MSMEs face significant challenges in adopting digital technology for their business development. The study was conducted using a descriptive qualitative method involving 50 MSME actors in Padang Sari Village as respondents. Data collection was carried out through direct observation, in-depth interviews, and documentation studies over a period of 6 months. The results of the study showed that the implementation of digital marketing strategies succeeded in increasing market reach by up to 150% and average turnover by 75%. The main obstacles identified included limited digital infrastructure, lack of understanding of technology, and minimal competent human resources. This study produces recommendations in the form of a digital marketing implementation framework that is adjusted to the characteristics of rural MSMEs, including the development of digital presence, optimization of social media, e-commerce integration, and sustainable HR capacity development programs.